The design and implementation of automated maintenance system for the first-wall based on dual-arm manipulator - Ke Wu; Jun Zhang; Yong Cheng; Qingxi Yang; Hongtao Pan; Tao Wang; Aiming Liu; Hao Han (Nuclear Engineering and Technology)
This paper proposed a framework of a dual-arm-based robotic maintenance system, including visual recognition, trajectory planning, force feedback control and master–slave control. To meet the requirements of automated maintenance, we proposed an improved design for the structures of the first wall tiles and support boards, and established a complete communication structure for the maintenance system that can adapt to different hardware versions. Based on the proposed framework, an experimental platform with dual-arm manipulator was established to demonstrate the maintenance scenario of the FW of the blanket in Vacuum Vessel (VV). The experimental result verified the feasibility of automated robotic maintenance system applied to the future fusion reactor.